Green supply chain management practices and organizational performance : an empirical study in Malaysian manufacturing firms - Tan, Cheng Ling; Yeo, Sook Fern; Low, Chea Huat (Penerbit Universiti Kebangsaan Malaysia, 2018)
This study aims to examine the influence of green supply chain management practices (GSCMP) and manufacturing capabilities on organizational performances. A quantitative method was used with the data obtained from the sample of 103 large manufacturing firms listed in the Federation of Malaysia Manufacturers (FMM). Smart-PLS 3.0 software was employed to confirm the data validity and reliability, and test the structural path modeling. This implies that GSCMP with manufacturing capabilities as the mediator is important to foster the organizational performance among manufacturing firms. A total of 103 manufacturing companies in Malaysia participated in this study with a response rate of 18%. It shows that only eight sub-hypotheses out of thirteen sub-hypotheses were supported, and the remaining five sub-hypotheses were not supported. The conclusion of this study provides the theoretical and practical implications as well as suggestions for future studies in different industries such as service, tourism and information technology.